A pultruded epoxy resin composition for wind turbine blades
Patent Information
- Application Number
- CN202210017331.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-07
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-01-07
AI Technical Summary
The epoxy resin-based fiber-reinforced composite materials used in wind power blades have the problem of insufficient mechanical strength, which seriously restricts the development of the wind power industry.
Using a pultruded epoxy resin composition for wind-powered blades, the mechanical properties of the composition are significantly improved by adding pretreated chopped glass fibers to the epoxy resin and synergistically treated with Ti3C2Tx MXene pretreatment liquid.
The mechanical properties of the epoxy resin composition are significantly improved, and the mechanical properties requirements of wind power blades can be met, and the overall performance of wind power blades is improved.
Smart Images

Figure BDA0003460305780000091
Abstract
Description
Technical Field
[0001] The invention relates to a pultruded epoxy resin composition for wind turbine blades, belonging to the technical field of epoxy resins. Background Art
[0002] Wind power generation refers to the conversion of wind kinetic energy into electrical energy. Wind energy is a clean, pollution-free renewable energy source that has been used by people for a long time, mainly through windmills to pump water and grind flour. People are interested in how to use wind to generate electricity. Using wind power to generate electricity is very environmentally friendly, and the amount of wind energy is huge, so it is increasingly valued by countries around the world.
[0003] Wind power generation is the process of converting the kinetic energy of wind into mechanical energy, and then converting the mechanical energy into electrical energy. The principle of wind power generation is to use wind power to drive the windmill blades to rotate, and then increase the speed of rotation through a speed increaser to drive the generator to generate electricity. According to windmill technology, power generation can begin at a breeze speed of about three meters per second (the degree of a breeze). Wind power generation is becoming a trend in the world because it does not require the use of fuel and does not produce radiation or air pollution.
[0004] The device required for wind power generation is called a wind turbine. This type of wind turbine can be roughly divided into three parts: the wind rotor (including the tail rudder), the generator and the tower. The wind rotor is an important component that converts the kinetic energy of wind into mechanical energy. It is composed of several blades. When the wind blows towards the blades, the aerodynamic force generated on the blades drives the wind rotor to rotate. The blades are the most basic and most critical components of wind turbines. The large-scale and high-power development of wind power blades has put forward higher requirements on the molding process and mechanical properties (mainly toughness and strength) of composite materials. Epoxy resin-based fiber-reinforced composite materials are the main materials for wind power blades and blade roots, but there are generally problems such as insufficient mechanical strength, which seriously restricts the development of the wind power industry. Summary of the invention
[0005] In view of the above defects, the technical problem solved by the present invention is to provide a pultruded epoxy resin composition for wind turbine blades with good mechanical properties.
[0006] The pultruded epoxy resin composition for wind turbine blades of the present invention comprises the following components in parts by weight: 80 to 120 parts of epoxy resin, 65 to 85 parts of curing agent, and 5 to 10 parts of pretreated chopped glass fibers; wherein the pretreated chopped glass fibers are prepared by the following method: 10 to 20 parts of chopped glass fibers are added with 60 to 80 parts of Ti3C2T xIn the MXene pretreatment liquid, microwave and ultrasonic waves are simultaneously turned on for synergistic treatment for 30 to 45 minutes; then the pretreated chopped glass fibers are taken out and dried to obtain the pretreated short glass fibers; the microwave power is 150 to 300 W; the ultrasonic power is 300 to 500 W, and the ultrasonic frequency is 45 to 65 KHz; the treatment temperature is 45 to 55 ° C; the Ti3C2T x The MXene pretreatment solution includes the following components in parts by weight: Ti3C2T x 6 to 8 parts of MXene compound, 80 to 100 parts of deionized water, 10 to 12 parts of propanol, and 15 to 20 parts of dopamine hydrochloride solution, wherein the concentration of dopamine hydrochloride in the dopamine hydrochloride solution is 5 to 8 g / L.
[0007] In one embodiment of the present invention, the microwave power is 150 W; the ultrasonic power is 300 W, the ultrasonic frequency is 45 KHz; and the treatment temperature is 45°C.
[0008] In one embodiment of the present invention, the Ti3C2T x The MXene compound is prepared by the following method: adding titanium carbide powder, titanium hydride powder, aluminum powder and stainless steel grinding balls into a low-temperature ball mill, introducing liquid nitrogen into the low-temperature ball mill so that the materials and the stainless steel grinding balls are completely immersed in the liquid nitrogen, ball milling to obtain a mixed powder, heating the mixed powder to 1300-1500°C at a rate of 1-6°C / min under a protective atmosphere, keeping the temperature, and then cooling to room temperature in a furnace, crushing to obtain Ti3AlC2 powder; immersing the Ti3AlC2 powder in an HF solution, stirring at room temperature for 20-26 hours, taking the solid, washing, and drying to obtain Ti3C2T x MXene compounds.
[0009] In a specific embodiment, the mass ratio of the titanium carbide powder, the titanium hydride powder and the aluminum powder is 6.5-7.5:2.5-3.5:1.5-2.5.
[0010] In a specific embodiment, based on a concentration of 40wt% of the HF solution, the mass volume ratio of the Ti3AlC2 powder to the HF solution is 1g:10-20mL. In a preferred embodiment, the mass volume ratio of the Ti3AlC2 powder to the HF solution is 1g:15mL.
[0011] In a specific embodiment, the ball milling speed is 300-400 rpm, the ball-to-material ratio is 1:0.8-1.2, and the diameter of the stainless steel grinding balls is 0.5-1.5 mm. In a preferred embodiment, the ball-to-material ratio is 1:1, and the diameter of the stainless steel grinding balls is 1 mm.
[0012] Preferably, in Ti3C2T xIn the preparation of MXene compounds, after drying, the following steps are further performed: using a low-temperature plasma treatment instrument to treat the dried T i3 C2T x The MXene compound is treated for 1 to 3 minutes; the atmosphere of the low-temperature plasma treatment instrument is a mixed gas of argon and nitrogen; the frequency of the low-temperature plasma treatment instrument is 35 to 65 KHz, the power is 80 to 120 W, the pressure of the atmosphere is 10 to 30 Pa, and the temperature is room temperature.
[0013] Furthermore, the pultruded epoxy resin composition for wind turbine blades of the present invention further comprises at least one of a diluent, an accelerator, a toughening agent, nano-silicon dioxide, a defoaming agent and a release agent.
[0014] In a specific embodiment, the pultruded epoxy resin composition for wind turbine blades includes the following components in parts by weight: 80-120 parts of epoxy resin, 2-4 parts of diluent, 65-85 parts of curing agent, 0.5-2.5 parts of accelerator, 5-10 parts of pretreated chopped glass fiber, 3-7 parts of toughening agent, 2-4 parts of nano-silicon dioxide, 1-4 parts of defoaming agent, and 0.3-1 part of release agent.
[0015] In a specific embodiment, the pultruded epoxy resin composition for wind turbine blades includes the following components in parts by weight: 100 parts of epoxy resin, 3 parts of diluent, 80 parts of curing agent, 1.5 parts of accelerator, 8 parts of pretreated chopped glass fiber, 4 parts of toughening agent, 3 parts of nano-silica, 3 parts of defoaming agent, and 0.8 parts of release agent.
[0016] In a specific embodiment, the pultruded epoxy resin composition for wind turbine blades is composed of the following components in parts by weight: 80-120 parts of epoxy resin, 2-4 parts of diluent, 65-85 parts of curing agent, 0.5-2.5 parts of accelerator, 5-10 parts of pretreated chopped glass fiber, 3-7 parts of toughening agent, 2-4 parts of nano-silicon dioxide, 1-4 parts of defoaming agent, and 0.3-1 part of release agent.
[0017] In a specific embodiment, the pultruded epoxy resin composition for wind turbine blades is composed of the following components in parts by weight: 100 parts of epoxy resin, 3 parts of diluent, 80 parts of curing agent, 1.5 parts of accelerator, 8 parts of pretreated chopped glass fiber, 4 parts of toughening agent, 3 parts of nano-silica, 3 parts of defoaming agent, and 0.8 parts of release agent.
[0018] Epoxy resins, curing agents, diluents, accelerators, toughening agents, nano-silica, defoamers and release agents commonly used in the art can all be applied to the present invention. In some embodiments, the epoxy resin is a bisphenol A epoxy resin and a bisphenol F epoxy resin in a weight ratio of 3 to 6:1; the diluent is any one of hexanediol diglycidyl ether and polypropylene glycol diglycidyl ether; the curing agent is one or a combination of two of tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, terpene anhydride, and nadic anhydride; the accelerator is one or a combination of two of N,N-dimethylbenzylamine, 1-methylimidazole, and 2-ethyl-4-methylimidazole; the toughening agent is polyethylene glycol diglycidyl ether and / or polyurethane; the defoamer is polysiloxane; and the release agent is zinc stearate and fluorophosphate alcohol ester in a mass ratio of 2:1.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The pretreated chopped glass fibers are added to the pultruded epoxy resin composition for wind turbine blades of the present invention, which can significantly improve the mechanical properties of the epoxy resin composition and meet the mechanical property requirements of the pultruded epoxy resin composition for wind turbine blades. DETAILED DESCRIPTION
[0021] The pultruded epoxy resin composition for wind turbine blades of the present invention comprises the following components in parts by weight: 80 to 120 parts of epoxy resin, 65 to 85 parts of curing agent, and 5 to 10 parts of pretreated chopped glass fibers; wherein the pretreated chopped glass fibers are prepared by the following method: 10 to 20 parts of chopped glass fibers are added with 60 to 80 parts of Ti3C2T x In the MXene pretreatment liquid, microwave and ultrasonic waves are simultaneously turned on for synergistic treatment for 30 to 45 minutes; then the pretreated chopped glass fibers are taken out and dried to obtain the pretreated short glass fibers; the microwave power is 150 to 300 W; the ultrasonic power is 300 to 500 W, and the ultrasonic frequency is 45 to 65 KHz; the treatment temperature is 45 to 55 ° C; the Ti3C2T x The MXene pretreatment solution includes the following components in parts by weight: Ti3C2T x 6 to 8 parts of MXene compound, 80 to 100 parts of deionized water, 10 to 12 parts of propanol, and 15 to 20 parts of dopamine hydrochloride solution, wherein the concentration of dopamine hydrochloride in the dopamine hydrochloride solution is 5 to 8 g / L.
[0022] The present invention adds specific pretreated chopped glass fibers to the pultruded epoxy resin composition for wind turbine blades, which can significantly improve the mechanical properties of the epoxy resin composition and meet the mechanical property requirements of the pultruded epoxy resin composition for wind turbine blades.
[0023] Among them, chopped glass fiber is also called glass fiber chopped strands. It is made of quartz sand melted at high temperature, drawn with a special impregnating agent (softener), and chopped online by wet method, or chopped product glass fiber.
[0024] Ti3C2T x MXene compounds are a class of two-dimensional transition metal carbides and nitrides with unique physical and chemical properties. During the synthesis of MXene, a variety of surface-terminated functional groups Tx (such as -O, -OH, -F) are formed on the outer surface of the transition metal, where x generally refers to the number of functional groups; Ti3C2T x There are a large number of oxygen-containing functional groups on the surface of MXene, Ti3C2T x The strong polarity of MXene surface and the x The combination of other components in the MXene pretreatment solution is more conducive to bonding with the glass fiber surface and bonding with the epoxy resin, thereby improving the mechanical properties of the epoxy resin composition.
[0025] Ti3C2T commonly used in this field x MXene compounds are suitable for the present invention. In one embodiment of the present invention, the Ti3C2T x The MXene compound is prepared by the following method: adding titanium carbide powder, titanium hydride powder, aluminum powder and stainless steel grinding balls into a low-temperature ball mill, introducing liquid nitrogen into the low-temperature ball mill so that the materials and the stainless steel grinding balls are completely immersed in the liquid nitrogen, ball milling to obtain a mixed powder, heating the mixed powder to 1300-1500°C at a rate of 1-6°C / min under a protective atmosphere, keeping the temperature, and then cooling to room temperature in a furnace, crushing to obtain Ti3AlC2 powder; immersing the Ti3AlC2 powder in an HF solution, stirring at room temperature for 20-26 hours, taking the solid, washing, and drying to obtain Ti3C2T x MXene compounds.
[0026] The protective atmosphere described in the present invention is an atmosphere that does not participate in the reaction, including but not limited to inert gas protection, etc.
[0027] The dopamine hydrochloride solutions of the present invention are all aqueous solutions, with water as the solvent.
[0028] In a specific embodiment, the microwave power is 150 W; the ultrasonic power is 300 W, the ultrasonic frequency is 45 KHz; and the treatment temperature is 45°C.
[0029] In a specific embodiment, the mass ratio of the titanium carbide powder, the titanium hydride powder and the aluminum powder is 6.5-7.5:2.5-3.5:1.5-2.5.
[0030] In a specific embodiment, based on a concentration of 40 wt% of the HF solution, the mass volume ratio of the Ti3AlC2 powder to the HF solution is 1 g: 10-20 mL. Preferably, the mass volume ratio of the Ti3AlC2 powder to the HF solution is 1 g: 15 mL.
[0031] In a specific embodiment, the ball milling speed is 300-400 rpm, the ball-to-material ratio is 1:0.8-1.2, and the diameter of the stainless steel grinding balls is 0.5-1.5 mm. Preferably, the ball-to-material ratio is 1:1, and the diameter of the stainless steel grinding balls is 1 mm.
[0032] Preferably, in Ti3C2T x In the preparation of MXene compounds, after drying, the following steps are further performed: using a low-temperature plasma treatment instrument to treat the dried T i3 C2T x The MXene compound is treated for 1 to 3 minutes; the atmosphere of the low-temperature plasma treatment instrument is a mixed gas of argon and nitrogen; the frequency of the low-temperature plasma treatment instrument is 35 to 65 KHz, the power is 80 to 120 W, the pressure of the atmosphere is 10 to 30 Pa, and the temperature is room temperature.
[0033] Furthermore, the pultruded epoxy resin composition for wind turbine blades of the present invention further comprises at least one of a diluent, an accelerator, a toughening agent, nano-silicon dioxide, a defoaming agent and a release agent.
[0034] In a specific embodiment, the pultruded epoxy resin composition for wind turbine blades includes the following components in parts by weight: 80-120 parts of epoxy resin, 2-4 parts of diluent, 65-85 parts of curing agent, 0.5-2.5 parts of accelerator, 5-10 parts of pretreated chopped glass fiber, 3-7 parts of toughening agent, 2-4 parts of nano-silicon dioxide, 1-4 parts of defoaming agent, and 0.3-1 part of release agent.
[0035] In a specific embodiment, the pultruded epoxy resin composition for wind turbine blades includes the following components in parts by weight: 100 parts of epoxy resin, 3 parts of diluent, 80 parts of curing agent, 1.5 parts of accelerator, 8 parts of pretreated chopped glass fiber, 4 parts of toughening agent, 3 parts of nano-silica, 3 parts of defoaming agent, and 0.8 parts of release agent.
[0036] In a specific embodiment, the pultruded epoxy resin composition for wind turbine blades is composed of the following components in parts by weight: 80-120 parts of epoxy resin, 2-4 parts of diluent, 65-85 parts of curing agent, 0.5-2.5 parts of accelerator, 5-10 parts of pretreated chopped glass fiber, 3-7 parts of toughening agent, 2-4 parts of nano-silicon dioxide, 1-4 parts of defoaming agent, and 0.3-1 part of release agent.
[0037] In a specific embodiment, the pultruded epoxy resin composition for wind turbine blades is composed of the following components in parts by weight: 100 parts of epoxy resin, 3 parts of diluent, 80 parts of curing agent, 1.5 parts of accelerator, 8 parts of pretreated chopped glass fiber, 4 parts of toughening agent, 3 parts of nano-silica, 3 parts of defoaming agent, and 0.8 parts of release agent.
[0038] Epoxy resins, curing agents, diluents, accelerators, toughening agents, nano-silica, defoamers and release agents commonly used in the art can all be applied to the present invention. In some embodiments, the epoxy resin is a bisphenol A epoxy resin and a bisphenol F epoxy resin in a weight ratio of 3 to 6:1; the diluent is any one of hexanediol diglycidyl ether and polypropylene glycol diglycidyl ether; the curing agent is one or a combination of two of tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, terpene anhydride, and nadic anhydride; the accelerator is one or a combination of two of N,N-dimethylbenzylamine, 1-methylimidazole, and 2-ethyl-4-methylimidazole; the toughening agent is polyethylene glycol diglycidyl ether and / or polyurethane; the defoamer is polysiloxane; and the release agent is zinc stearate and fluorophosphate alcohol ester in a mass ratio of 2:1.
[0039] The specific implementation modes of the present invention are further described below in conjunction with embodiments, but the present invention is not limited to the scope of the embodiments.
[0040] Example 1
[0041] 1. Preparation of Ti3C2T x MXene compounds
[0042] 7.187g titanium carbide powder, 2.953g titanium hydride powder, 1.781g aluminum powder and stainless steel grinding balls were added to a low-temperature ball mill, and liquid nitrogen was introduced into the low-temperature ball mill so that the materials and stainless steel grinding balls were completely immersed in liquid nitrogen. The ball mill was milled for 5 hours at a speed of 300rpm. The ball-to-material ratio was 1:1. The diameter of the stainless steel grinding balls was 1mm. A mixed powder was obtained. The mixed powder was heated to 200°C at a heating rate of 5°C / min in an argon atmosphere in a tubular furnace, and kept warm for 15min. Then, it was heated to 900°C at a heating rate of 5°C / min in an argon atmosphere, and kept warm for 30min. Then, it was heated to 1400°C at a heating rate of 2°C / min in an argon atmosphere, and kept warm for 80min. The mixture was cooled to room temperature in the furnace, and the obtained block was broken and ground, and sieved with a 400-mesh sieve to obtain Ti3AlC2 powder. 3g Ti3AlC2 powder was immersed in 45mL HF solution (40 wt%) was added and stirred at room temperature for 24 h. The obtained suspension was centrifuged and washed with ultrapure water until the pH value was greater than 6.0. The obtained precipitate was dried under vacuum at 60 °C to obtain Ti3C2T xMXene compounds (prepared multiple times using this method to obtain the desired quality of Ti3C2T x MXene compounds).
[0043] 2. Preparation of Ti3C2T x MXene pretreatment solution
[0044] Ti3C2T x 6 kg of MXene compound, 80 kg of deionized water, 10 kg of propanol, and 15 kg of dopamine hydrochloride solution with a concentration of 5 g / L were mixed to obtain Ti3C2T x MXene pretreatment solution.
[0045] 3. Preparation of pretreated chopped glass fibers
[0046] 10 kg of chopped glass fiber (length 2 mm, diameter 6 μm) was added to 60 kg of Ti3C2T x The MXene pretreatment liquid was added into a microwave-ultrasonic integrated reactor at the same time, and microwave and ultrasonic waves were turned on for coordinated treatment for 30 minutes, with a microwave power of 150 W, an ultrasonic power of 300 W, and an ultrasonic frequency of 45 KHz. The treatment temperature was 45 ° C. After treatment, the fiber was taken out and dried to obtain pretreated chopped glass fiber.
[0047] 4. Preparation of pultruded epoxy resin composition for wind turbine blades
[0048] Weigh the following raw materials in proportion:
[0049] Epoxy resin 80kg, diluent 2kg, curing agent 85kg, accelerator 0.5kg, pretreated chopped glass fiber 5kg, toughening agent 3kg, nano-silica 2kg, defoamer 1kg, release agent 0.3kg;
[0050] Among them, the epoxy resin is bisphenol A epoxy resin and bisphenol F epoxy resin in a weight ratio of 4:1; the diluent is hexanediol diglycidyl ether; the curing agent is methyltetrahydrophthalic anhydride; the accelerator is N,N-dimethylbenzylamine; the toughening agent is polyethylene glycol diglycidyl ether; the defoaming agent is polysiloxane; and the release agent is zinc stearate and fluoroalcohol phosphate in a mass ratio of 2:1.
[0051] The diluent, accelerator, toughening agent, defoamer and release agent were mixed, stirred for 30 minutes, and allowed to stand for 30 minutes to obtain a mixture;
[0052] Add epoxy resin into the reaction kettle, control the temperature at 55°C, add the curing agent and the mixture, add the mixture of pretreated chopped glass fibers and nano-silicon dioxide while stirring, continue stirring for 60 minutes after the addition is completed, and obtain a pultruded epoxy resin composition for wind turbine blades.
[0053] Example 2
[0054] 1. Preparation of Ti3C2T x MXene compounds
[0055] Ti3C2T was prepared by the method of Example 1. x MXene compounds.
[0056] 2. Preparation of Ti3C2T x MXene pretreatment solution
[0057] Ti3C2T x 8 kg of MXene compound, 80 kg of deionized water, 10 kg of propanol, and 20 kg of dopamine hydrochloride solution with a concentration of 8 g / L were mixed to obtain Ti3C2T x MXene pretreatment solution.
[0058] 3. Preparation of pretreated chopped glass fibers
[0059] 15 kg of chopped glass fiber (length 2 mm, diameter 6 μm) was added to 65 kg of Ti3C2T x The MXene pretreatment liquid was added into a microwave-ultrasonic integrated reactor at the same time, and microwave and ultrasonic waves were turned on for coordinated treatment for 30 minutes, with a microwave power of 150 W, an ultrasonic power of 300 W, and an ultrasonic frequency of 45 KHz. The treatment temperature was 45 ° C. After treatment, the fiber was taken out and dried to obtain pretreated chopped glass fiber.
[0060] 4. Preparation of pultruded epoxy resin composition for wind turbine blades
[0061] Weigh the following raw materials in proportion:
[0062] Epoxy resin 100kg, diluent 3kg, curing agent 80kg, accelerator 1.5kg, pre-treated chopped glass fiber 8kg, toughening agent 4kg, nano-silicon dioxide 3kg, defoaming agent 3kg, release agent 0.8kg;
[0063] Among them, the epoxy resin is bisphenol A epoxy resin and bisphenol F epoxy resin in a weight ratio of 4:1; the diluent is hexanediol diglycidyl ether; the curing agent is methyl hexahydrophthalic anhydride; the accelerator is 2-ethyl-4-methylimidazole; the toughening agent is polyethylene glycol diglycidyl ether; the defoaming agent is polysiloxane; and the release agent is zinc stearate and fluoroalcohol phosphate in a mass ratio of 2:1.
[0064] The diluent, accelerator, toughening agent, defoamer and release agent were mixed, stirred for 30 minutes, and allowed to stand for 30 minutes to obtain a mixture;
[0065] Add epoxy resin into the reaction kettle, control the temperature at 55°C, add the curing agent and the mixture, add the mixture of pretreated chopped glass fibers and nano-silicon dioxide while stirring, continue stirring for 60 minutes after the addition is completed, and obtain a pultruded epoxy resin composition for wind turbine blades.
[0066] Example 3
[0067] 1. Preparation of Ti3C2T x MXene compounds
[0068] Ti3C2T was obtained by the method of Example 1. x MXene compound, and then the obtained Ti3C2T x The MXene compound was reprocessed for 2 min to obtain the reprocessed Ti3C2T x MXene compound; the atmosphere of the low-temperature plasma treatment instrument is a mixed gas of argon and nitrogen; the frequency of the low-temperature plasma treatment instrument is 45KHz, the power is 120W, the atmosphere pressure is 20Pa, and the temperature is room temperature.
[0069] 2. Preparation of Ti3C2T x MXene pretreatment solution
[0070] The reprocessed Ti3C2T x 8 kg of MXene compound, 80 kg of deionized water, 10 kg of propanol, and 20 kg of dopamine hydrochloride solution with a concentration of 8 g / L were mixed to obtain Ti3C2T x MXene pretreatment solution.
[0071] 3. Preparation of pretreated chopped glass fibers
[0072] 15 kg of chopped glass fiber (length 2 mm, diameter 6 μm) was added to 65 kg of Ti3C2T xThe MXene pretreatment liquid was added into a microwave-ultrasonic integrated reactor at the same time, and microwave and ultrasonic waves were turned on for coordinated treatment for 30 minutes, with a microwave power of 150 W, an ultrasonic power of 300 W, and an ultrasonic frequency of 45 KHz. The treatment temperature was 45 ° C. After treatment, the fiber was taken out and dried to obtain pretreated chopped glass fiber.
[0073] 4. Preparation of pultruded epoxy resin composition for wind turbine blades
[0074] Weigh the following raw materials in proportion:
[0075] Epoxy resin 100kg, diluent 3kg, curing agent 80kg, accelerator 1.5kg, pre-treated chopped glass fiber 8kg, toughening agent 4kg, nano-silicon dioxide 3kg, defoaming agent 3kg, release agent 0.8kg;
[0076] Among them, the epoxy resin is bisphenol A epoxy resin and bisphenol F epoxy resin in a weight ratio of 4:1; the diluent is hexanediol diglycidyl ether; the curing agent is methyl hexahydrophthalic anhydride; the accelerator is 2-ethyl-4-methylimidazole; the toughening agent is polyethylene glycol diglycidyl ether; the defoaming agent is polysiloxane; and the release agent is zinc stearate and fluoroalcohol phosphate in a mass ratio of 2:1.
[0077] The diluent, accelerator, toughening agent, defoamer and release agent were mixed, stirred for 30 minutes, and allowed to stand for 30 minutes to obtain a mixture;
[0078] Add epoxy resin into the reaction kettle, control the temperature at 55°C, add the curing agent and the mixture, add the mixture of pretreated chopped glass fibers and nano-silicon dioxide while stirring, continue stirring for 60 minutes after the addition is completed, and obtain a pultruded epoxy resin composition for wind turbine blades.
[0079] Comparative Example 1
[0080] Weigh the following raw materials in proportion:
[0081] Epoxy resin 100kg, diluent 3kg, curing agent 80kg, accelerator 1.5kg, chopped glass fiber (length 2mm, diameter 6μm) 8kg, toughening agent 4kg, nano-silicon dioxide 3kg, defoaming agent 3kg, release agent 0.8kg;
[0082] Among them, the epoxy resin is bisphenol A epoxy resin and bisphenol F epoxy resin in a weight ratio of 4:1; the diluent is hexanediol diglycidyl ether; the curing agent is methyl hexahydrophthalic anhydride; the accelerator is 2-ethyl-4-methylimidazole; the toughening agent is polyethylene glycol diglycidyl ether; the defoaming agent is polysiloxane; and the release agent is zinc stearate and fluoroalcohol phosphate in a mass ratio of 2:1.
[0083] The diluent, accelerator, toughening agent, defoamer and release agent were mixed, stirred for 30 minutes, and allowed to stand for 30 minutes to obtain a mixture;
[0084] Add epoxy resin into the reaction kettle, control the temperature at 55°C, add the curing agent and the mixture, add the mixture of chopped glass fiber and nano-silicon dioxide while stirring, continue stirring for 60 minutes after the addition is completed, and obtain a pultruded epoxy resin composition for wind turbine blades.
[0085] Comparative Example 2
[0086] Weigh the following raw materials in proportion:
[0087] Epoxy resin 120kg, diluent 4kg, curing agent 85kg, accelerator 2kg, chopped glass fiber (length 2mm, diameter 6μm) 10kg, toughening agent 6kg, nano-silicon dioxide 3.5kg, defoaming agent 2.5kg, release agent 1kg;
[0088] Among them, the epoxy resin is bisphenol A epoxy resin and bisphenol F epoxy resin in a weight ratio of 4:1; the diluent is hexanediol diglycidyl ether; the curing agent is methyl hexahydrophthalic anhydride; the accelerator is 2-ethyl-4-methylimidazole; the toughening agent is polyethylene glycol diglycidyl ether; the defoaming agent is polysiloxane; and the release agent is zinc stearate and fluoroalcohol phosphate in a mass ratio of 2:1.
[0089] The diluent, accelerator, toughening agent, defoamer and release agent were mixed, stirred for 30 minutes, and allowed to stand for 30 minutes to obtain a mixture;
[0090] Add epoxy resin into the reaction kettle, control the temperature at 55°C, add the curing agent and the mixture, add the mixture of chopped glass fiber and nano-silicon dioxide while stirring, continue stirring for 60 minutes after the addition is completed, and obtain a pultruded epoxy resin composition for wind turbine blades.
[0091] The pultruded epoxy resin compositions for wind turbine blades of Examples 1 to 3 and Comparative Examples 1 to 2 were used to prepare pure epoxy resin materials (ER) and epoxy resin composite materials containing glass fibers (GF-ER) were prepared by pultrusion molding; and the mechanical properties of the two materials were tested; three samples were taken for each material, each sample was tested 3 times, and the results were averaged; ISO 527, ISO 178 and GB32377-2015 were used to test the tensile, bending and impact properties of pure epoxy resin materials and epoxy resin composite materials containing glass fibers prepared by pultrusion molding, and the results are shown in Table 1 (mechanical properties of pure epoxy resin materials) and Table 2 (mechanical properties of epoxy resin composite materials containing glass fibers);
[0092] Among them, the preparation method of pure epoxy resin material is: cast the pultruded epoxy resin composition for wind turbine blades prepared in each embodiment and comparative example into a mold, and then heat-cured at 95°C for 1h, 155°C for 1.5h, and 175°C for 1.5h in sequence; after demolding, cut into standard test pieces for performance testing, the results are shown in Table 1.
[0093] Table 1
[0094] <![CDATA[Impact strength (kJ / m 2 )]]> Tensile strength(MPa) Tensile modulus(GPa) Example 1 28.4 70.3 3.16 Example 2 28.3 70.2 3.15 Example 3 29.8 72.8 3.29 Comparative Example 1 20.5 59.8 2.62 Comparative Example 2 20.2 59.6 2.71
[0095] The preparation method of the epoxy resin composite material containing glass fiber is as follows: the pultruded epoxy resin composition for wind turbine blades prepared in each embodiment and comparative example is injected into the dipping tank of the pultrusion molding equipment, and the glass fiber is sequentially passed through the dipping tank, the preforming die and the pultrusion molding die to prepare the epoxy resin composite material containing glass fiber. The pultrusion molding die includes three areas: a preheating zone, a gel zone and a curing zone. A gradient heating method is adopted, and the temperature is controlled at 95, 155 and 175°C respectively. The pultrusion speed is 22 cm / min, and the volume content of the glass fiber is 60%. The results are shown in Table 2.
[0096] Table 2
[0097]
[0098] It can be seen that adding pretreated chopped glass fibers to the pultruded epoxy resin composition for wind turbine blades of the present invention can significantly improve the mechanical properties of the epoxy resin composition.
Claims
1. A pultruded epoxy resin composition for wind turbine blades, characterized in that: The invention comprises the following components in parts by weight: 80 to 120 parts of epoxy resin, 65 to 85 parts of curing agent, and 5 to 10 parts of pretreated chopped glass fibers; The pretreated chopped glass fibers are prepared by the following method: 10 to 20 parts of chopped glass fibers are added with 60 to 80 parts of Ti3C2T x In the MXene pretreatment liquid, microwave and ultrasonic waves are simultaneously turned on for synergistic treatment for 30 to 45 minutes; then the pretreated chopped glass fibers are taken out and dried to obtain the pretreated short glass fibers; the microwave power is 150 to 300 W; the ultrasonic power is 300 to 500 W, and the ultrasonic frequency is 45 to 65 KHz; the treatment temperature is 45 to 55°C; The Ti3C2T x The MXene pretreatment solution includes the following components in parts by weight: Ti3C2T x 6 to 8 parts of MXene compound, 80 to 100 parts of water, 10 to 12 parts of propanol, and 15 to 20 parts of dopamine hydrochloride solution, wherein the concentration of dopamine hydrochloride in the dopamine hydrochloride solution is 5 to 8 g / L.
2. The pultruded epoxy resin composition for wind turbine blades according to claim 1, characterized in that: The microwave power was 150W; the ultrasonic power was 300W, the ultrasonic frequency was 45KHz; and the processing temperature was 45°C.
3. The pultruded epoxy resin composition for wind turbine blades according to claim 1, characterized in that: Ti3C2T x The MXene compound is prepared by the following method: adding titanium carbide powder, titanium hydride powder, aluminum powder and stainless steel grinding balls into a low-temperature ball mill, introducing liquid nitrogen into the low-temperature ball mill so that the materials and the stainless steel grinding balls are completely immersed in the liquid nitrogen, ball milling to obtain a mixed powder, heating the mixed powder to 1300-1500°C at a rate of 1-6°C / min under a protective atmosphere, keeping the temperature, and then cooling to room temperature in a furnace, crushing to obtain Ti3AlC2 powder; immersing the Ti3AlC2 powder in an HF solution, stirring at room temperature for 20-26 hours, taking the solid, washing, and drying to obtain Ti3C2T x MXene compounds.
4. The pultruded epoxy resin composition for wind turbine blades according to claim 3, characterized in that: The mass ratio of the titanium carbide powder, the titanium hydride powder and the aluminum powder is 6.5-7.5:2.5-3.5:1.5-2.
5.
5. The pultruded epoxy resin composition for wind turbine blades according to claim 3, characterized in that: Assuming the concentration of HF solution is 40wt%, the mass volume ratio of Ti3AlC2 powder to HF solution is 1 g:10-20 mL.
6. The pultruded epoxy resin composition for wind turbine blades according to claim 5, characterized in that: The mass volume ratio of Ti3AlC2 powder to HF solution is 1 g:15 mL.
7. The pultruded epoxy resin composition for wind turbine blades according to claim 3, characterized in that: The ball milling speed is 300-400 rpm; the ball-to-material ratio is 1:0.8-1.2; and the diameter of the stainless steel grinding balls is 0.5-1.5 mm.
8. The pultruded epoxy resin composition for wind turbine blades according to claim 7, characterized in that: The ball-to-material ratio is 1:1; the diameter of the stainless steel grinding ball is 1 mm.
9. The pultruded epoxy resin composition for wind turbine blades according to claim 3, characterized in that: After drying, the following steps are performed: the dried Ti3C2T x The MXene compound is treated for 1 to 3 min; the atmosphere of the low-temperature plasma treatment instrument is a mixed gas of argon and nitrogen; the frequency of the low-temperature plasma treatment instrument is 35 to 65 KHz, the power is 80 to 120 W, the pressure of the atmosphere is 10 to 30 Pa, and the temperature is room temperature.
10. The pultruded epoxy resin composition for wind turbine blades according to claim 1, characterized in that: The pultruded epoxy resin composition for wind turbine blades further comprises at least one of a diluent, an accelerator, a toughening agent, nano silicon dioxide, a defoaming agent and a release agent.
11. The pultruded epoxy resin composition for wind turbine blades according to claim 10, characterized in that: The invention comprises the following components in parts by weight: 80-120 parts of epoxy resin, 2-4 parts of diluent, 65-85 parts of curing agent, 0.5-2.5 parts of accelerator, 5-10 parts of pretreated chopped glass fiber, 3-7 parts of toughening agent, 2-4 parts of nano silicon dioxide, 1-4 parts of defoaming agent and 0.3-1 parts of release agent.
12. The pultruded epoxy resin composition for wind turbine blades according to claim 11, characterized in that: The invention comprises the following components in parts by weight: 100 parts of epoxy resin, 3 parts of diluent, 80 parts of curing agent, 1.5 parts of accelerator, 8 parts of pretreated chopped glass fiber, 4 parts of toughening agent, 3 parts of nano silicon dioxide, 3 parts of defoaming agent and 0.8 parts of release agent.
13. The pultruded epoxy resin composition for wind turbine blades according to claim 1, characterized in that: The invention is composed of the following components in parts by weight: 80-120 parts of epoxy resin, 2-4 parts of diluent, 65-85 parts of curing agent, 0.5-2.5 parts of accelerator, 5-10 parts of pretreated chopped glass fiber, 3-7 parts of toughening agent, 2-4 parts of nano silicon dioxide, 1-4 parts of defoaming agent and 0.3-1 parts of release agent.
14. The pultruded epoxy resin composition for wind turbine blades according to claim 13, characterized in that: The invention is composed of the following components in parts by weight: 100 parts of epoxy resin, 3 parts of diluent, 80 parts of curing agent, 1.5 parts of accelerator, 8 parts of pretreated chopped glass fiber, 4 parts of toughening agent, 3 parts of nano silicon dioxide, 3 parts of defoaming agent and 0.8 parts of release agent.
15. The pultruded epoxy resin composition for wind turbine blades according to claim 11, characterized in that: The epoxy resin is bisphenol A epoxy resin and bisphenol F epoxy resin in a weight ratio of 3 to 6:1; the diluent is any one of hexanediol diglycidyl ether and polypropylene glycol diglycidyl ether; the curing agent is one or a combination of two of tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, terpene anhydride, and nadic anhydride; the accelerator is one or a combination of two of N,N-dimethylbenzylamine, 1-methylimidazole, and 2-ethyl-4-methylimidazole; the toughening agent is polyethylene glycol diglycidyl ether and / or polyurethane; the defoaming agent is polysiloxane; and the release agent is zinc stearate and fluoroalcohol phosphate in a mass ratio of 2:1.
Citation Information
Patent Citations
Microwave ultrasonic co-processing type chemical surface modification method and microwave ultrasonic co-processing type chemical surface modification device for carbon fiber
CN104032565A
High-performance pultrusion epoxy resin composite material for wind power and preparation method thereof
CN112795143A
MXene coated carbon fiber and preparation method thereof
CN113652858A